{eq}Y = f(x) =x^2 - 3x + 2, x = 5,DX = \Delta x = 0.2 {/eq}


{eq}Y = f(x) =x^2 - 3x + 2, x = 5,DX = \Delta x = 0.2 {/eq}

Change of Function:

Let's consider a function of one variable {eq}f(x). {/eq}

The change of the function from a point {eq}x_0 {/eq} to {eq}x_0+\Delta x {/eq} is {eq}\Delta y = f(x_0+\Delta x)- f(x_0). {/eq}

Answer and Explanation:

Become a Study.com member to unlock this answer!

View this answer

See full answer below.

Learn more about this topic:

Determine the Initial Value of a Function


Chapter 4 / Lesson 5

Learn the definition of the initial value of a function. Understand how to find the initial value. Using examples, practice calculating the initial value for the given function.

Related to this Question

Explore our homework questions and answers library